Yoga in Britain: stretching spirituality and educating yogis - Newcombe, Suzanne (Equinox Publishing Ltd, 2019)
Rethinking yoga -- The literary elite booksellers and publishers -- The self-taught yogis, adult education and the wheel of yoga -- Charismatic gurus in adult education -- Middle class women join evening classes -- Yoga in popular music and counter culture (the 60s and 70s) -- Yoga on the telly -- Yoga as therapy -- Diversity of practice and practitioners -- Yoga in Britain after the 1980s.